Genetic divergence between isolated populations of the North Island New Zealand Rifleman (Acanthisitta chloris granti) implicates ancient biogeographic impacts rather than recent habitat fragmentation. Issue 11 (4th May 2021) - Withers, Sarah J.; Parsons, Stuart; Hauber, Mark E.; Kendrick, Alistair; Lavery, Shane D.
Abstract: This research investigates the extent and causal mechanisms of genetic population divergence in a poorly flighted passerine, the North Island Rifleman or Titipounamu ( Acanthisitta chloris granti ). While this species has a historically widespread distribution, anthropogenic forest clearance has resulted in a highly fragmented current distribution. We conducted analyses of mitochondrial DNA (COI and Control Region) and 12 nuclear DNA microsatellites to test for population divergence and estimate times of divergence. DiyAbc and BioGeoBears were then used to assess likely past dispersal scenarios based on both mtDNA and nDNA. The results reveal several significantly divergent lineages across the North Island of New Zealand and indicate that some populations have been isolated for extensive periods of time (0.7–4.9 mya). Modeling indicated a dynamic history of population connectivity, with a drastic restriction in gene flow between three geographic regions, followed by a more recent re‐establishment of connectivity. Our analyses indicate the dynamic influence of key geological and climatological events on the distribution of genetic diversity in this species, including support for the genetic impact of old biogeographic boundaries such as the Taupo Line and Cockayne's Line, rather than recent anthropogenic habitat fragmentation. These findings present a rare example of an avian species with a genetic history more like that of flightless taxa and so provide new general insights into vicariant processes affecting populations of passerines with limited dispersal. Abstract : This research uncovers significant genetic divergence between populations of a basal passerine with restricted dispersal potential, New Zealand's North Island Rifleman. These results demonstrate the impact of ancient biogeographic events on the distribution of this species and present a rare example of an avian species with a genetic history more like that of flightless taxa. This work provides new insights into vicariant processes affecting populations of passerines with limited dispersal more broadly.